PERANCANGAN SISTEM INFORMASI BUKU TAMU PADA DISKOMINFO SERDANG BEDAGAI BERBASIS WEB - Buyung, Adnan; Sitompu, Surganda; Sitepu , Arjuna (Universitas Nusa Putra, 2024)
Using the Guest Book at the Serdang Bedagai Diskominfo Office is an important process that can make it easier to record data on guests who visit the Serdang Bedagai Diskominfo Office. The Guest Book functions to record the names and destinations of guests visiting the Serdang Bedagai Diskominfo Office. Seeing the importance of the Guest Book at the Serdang Bedagai Office, it is necessary to create a website that will help make it easier to record data on visiting guests, no longer needing to manually use paper. This Guest Book also functions to store important guest archives and data without fear of loss. By creating this system, it is hoped that it can overcome the problem of archiving visiting guest data to make it easier to find and better. The purpose of this research is to produce a website-based system that is used to manage guest book lists.